1997
DOI: 10.1037/0278-7393.23.6.1291
|View full text |Cite
|
Sign up to set email alerts
|

Episodic retrieval in negative priming and repetition priming.

Abstract: Subjects identified target letters flanked by incompatible distractor letters (e.g., ABA). Distractor onset was randomly simultaneous with target onset or was delayed by 400 ms. In Experiment 1, one third of probe-trial targets were identical to the preceding prime-trial distractor. Responses were slower to repeated letters than to unrepeated letters {negative priming) only when prime and probe trials shared the same distractor-onset conditions. In Experiment 2, one third of probe-trial targets were identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
360
14
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(403 citation statements)
references
References 111 publications
26
360
14
3
Order By: Relevance
“…Alternatively, memory retrieval has been proposed to account for negative priming (Neill, 1997;Neill & Mathis, 1998;Neill et al, 1992). This theoretical view can also account for the results of our experiments.…”
Section: Discussionsupporting
confidence: 71%
“…Alternatively, memory retrieval has been proposed to account for negative priming (Neill, 1997;Neill & Mathis, 1998;Neill et al, 1992). This theoretical view can also account for the results of our experiments.…”
Section: Discussionsupporting
confidence: 71%
“…One potential explanation of the n-2 task repetition cost that does not assume inhibition was explored by Mayr (2002). This episodic retrieval account (Neill, 1997) suggests (adapted to a task switching context) that when a task has been performed an episodic trace of trial parameters (such as the cue, stimulus characteristics, and the response made) is stored in memory. When this task is cued again, retrieval of the most recent episodic trace occurs.…”
Section: Public Significance Statementmentioning
confidence: 99%
“…If episodic retrieval is a primary determinant ofnegative priming, then priming should occur to the degree that there is similarity of context on prime and probe displays. Evidence for this has been presented in a recent study reported by Neill (1997). Subjects were required to identify a centrally located target letter while ignoring distracting letters on the left and the right of the target.…”
mentioning
confidence: 93%
“…As predicted by the episodic retrieval account, negative priming occurred only when the distractor onset matched across prime and probe displays (early/early, late/late). The logic of the present experiment is similar to that of Neill (1997), using a different manipulation of context. We wanted to test the hypothesis that a probe display will be a more effective retrieval cue when it is highly similar to the previous prime display, thus leading to more negative priming.…”
mentioning
confidence: 99%